Sharing of Resources in Real Time System for Multiple User: Enhancing Communication Performance through Resource Sharing in a Heterogeneous Internetwork (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Resource sharing is finest technique for big conferences. It provides real time presentation guaranteed. The recent approach to supporting real time communication assign network resources either individual links or to aggregates of links. Resource sharing is a new approach. We will discuss a fully distributed technique for using resource sharing to present guaranteed performance communication in a heterogeneous internetwork. Result prove that resource sharing leads to a big gain in the connection approval overhead associated with access control.